The Money Pump as a Measure of Revealed Preference Violations - Echenique, Federico; Lee, Sangmok; Shum, Matthew (Journal of Political Economy, 2011)
We introduce a measure of the severity of violations of the revealed preference axioms, the money pump index (MPI). The MPI is the amount of money one can extract from a consumer who violates the axioms. It is also a statistical test for the hypothesis that a consumer is rational when behavior is observed with error. We present an application using a panel data set of food expenditures. The data exhibit many violations of the axioms. Mostly, the MPI for these violations is small. The MPI indicates that the hypothesis of consumer rationality cannot be rejected.